LEGAL ASSISTANCE IN APPLYING FOR TRANSFER OF LAND RIGHTS SUBMISSIONS IN KANTOR NOTARIS & PPAT RIAN SUGITO, S.H., M.Kn. - Wulan Purnamasari; Abdurrakhman Alhakim (Universitas Internasional Batam, 2022)
Lands in Indonesia aren’t all managed by the capital and central government. Every region has institutions selected to manage and achieve rights to land managements. Specifically, in Batam, a body called Badan Pengusahaan Batam is the selected institution to conduct such function by the state. Rights to the land management also included rights to transfer of land rights through purchase and procurement, trade, participation of capital and bequest. This right include Rights to build and Rights to use. This usage of right must be followed title transfer when transfer of rights occur. These rights require written agreement from the institute that has the rights to the land management, which is BP Batam in te form of land transfer permission approval and within its development, the approval is requested and processed through an online system. BP Batam uses an application named Land Management System or LMS and its implementation isn’t fully effective. Based on this background, the author would like to conduct an assistance to apply for the request of land transfer permission approval and title transfer. The author will conduct observation to gather necessary data within the program.